Paradigm Shift Regarding The Meaning of Appearing Before a Notary in The Cyber Notary Context - Fidiyani, Nuraeni; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Paradigm shift can refer to a fundamental change in the form of perspective, mindset, or conceptual framework used to understand, explain, or solve a problem. The essence of cyber notary itself can be interpreted as a notary who carries out his duties or authority based on information technology, this is not only the legality of using a cell phone for communication between a notary and his client but also relates to the duties and functions of a notary, especially in making deeds. This study uses a normative legal research method. The approach methods in this study are the statutory approach, the conceptual approach, and the theoretical approach. The data sources used in this study are secondary data sources, while the data analysis used is prescriptive data analysis. The results of this study are First, regarding the paradigm shift regarding the meaning of appearing before a notary in the context of cyber notary, it cannot be described in detail and in detail how the shift takes place because the Notary Law, the Civil Code itself has not regulated the existence of digital face-to-face in the concept of cyber notary, so it can only be described roughly regarding the use of video teleconferences such as zoom, cameras, cell phones, CCTV but it is emphasized that the parties must remain present. Second, regarding legal certainty regarding deeds made in the cyber notary concept, it can be seen that there is no legal certainty because the Notary Law does not regulate notaries working as cyber notaries.Keywords: Cyber Notary; Facing Digitally; Paradigm Shift.